The Functional Criterion of Analytical Realism and the Operational Criterion of Operative Constructivism - Giordano, Pedro Martín (2024)
My response is organized around three thematic axes: the particu- larity of Luhmannian constructivism; the controversy around “there are systems”; and the comparison between analytical realism and operative constructivism.